A comparative analytical study of the kinematic transmission index values and some bio-kinematical variables for the stage of prompting of the long jump - Ibrahim, S. A.; William, W. L.; Sahib, H. M. A. (Journal of Human Sport & Exercise, 2021)
The importance of research showed in the study of some bio-kinematical variables of the long jump for younger heroes of the country and the comparison between them to reach the best performance through bio-kinematic careful analysis and thus get a clear picture contribute to improve the kinetic level and achievement together, The researchers conducted their experiment on two young country heroes of long jump using a video camera type (Sony( With tripod stand as well as a computer type( DELL) With its accessories as well as the software for imaging and biomechanical analysis, where six attempts were given to each player and the highest-achieving attempts were chosen for the analysis. The researchers reached several conclusions. The second jumper achieved superiority over his first counterpart by the velocity variable of the initial horizontal rise stage, but it moved away from its ideal value. Both jumpers achieved an angular transition to the centre of gravity of the body during the rise stage, which was similar by following the values of the angles of decline and rise, but the first jumper touched at a lower angle and left at a higher angle than the second jumper. The researchers concluded with several recommendations. The need to pay attention to the development of the qualities of speed and strength because of their role in achieving achievement with this effectiveness, the most important of which is the speed of the approach stage. Emphasis on reducing the rise time by achieving ideal angles for landing and rise as well as the amount of flexion of the knee joint during the stage.